STUDENTS’ READING COMPREHENSION SKILL: THE ROLES OF TEXT READABILITY AND QUESTION DIFFICULTY - Dirgantari, Alfi Suci; Susantiningdyah, Healty (PEOPLE: International Journal of Social Sciences, 2020)
This research is trying to investigate whether students’ difficulties in comprehending high-order questions are related to the readability of the reading text and the difficulty of the questions. The subjects in this research are freshmen in Institut Teknologi Kalimantan. Using random sampling, students with different levels of reading skills are chosen. This research asked students to answer reading comprehension tests, consisting of questions ranging from literal to evaluative questions, with reading texts ranging from easy to difficult. The result shows that in almost all levels of reading texts, inferential and evaluative reading questions are considered as the most difficult, as shown by the few numbers of correct answers. The level of text readability also influences students’ comprehension with the ‘easy’ text has the most correct answers and the ‘difficult’ text the least. It can be seen that students need to be introduced to a variety of texts and to be taught to answer questions with different levels of difficulty.